Investigations of the Montmorillonite and Aluminium Trihydrate Addition Effects on the Ignitability and Thermal Stability of Asphalt - Kai Zhu; Ke Wu; Bin Wu; Zhiyi Huang (Journal of Chemistry)
By means of limiting oxygen index (LOI), cone calorimeter, and TG-DSC tests, this paper investigated the effect of unmodified montmorillonite (MMT), organically modified montmorillonite (OMMT), and aluminium trihydrate (ATH) additions on the flame retardancy for asphalt combustion. Experimental results showed that adding a small amount of montmorillonite did not significantly increase the oxygen index of the asphalt but reduced the heat release rate during asphalt combustion. TGA tests had indicated that the montmorillonite (MMT and OMMT) could suppress the release of flammable volatiles and form more asphaltenes, which hence postponed the burnout time of asphalt. Furthermore, the combination of montmorillonite (MMT and OMMT) and ATH had yielded a synergistic effect, which had further reduced the heat release rate and also increased the oxygen index of asphalt. In particular, after further addition of OMMT, the barrier layer showed less crack, leading to a significant decrease in the heat release rate as compared to the adding of ATH alone.